Classification of crude oil and its correlation with terrestrial plant inputs across different areas in the Xihu Depression, East China Sea Shelf basin: insights from organic geochemical evidence - Yuhan, Jiang; Ruibo, Guo; Dujie, Hou; Xiong, Cheng (Frontiers in Earth Science, 2025)
IntroductionWhile crude oils in the Xihu Depression are known to originate from terrestrial sources, a systematic classification linking their geochemistry to specific plant inputs has been lacking. This study utilizes detailed organic geochemistry to classify these oils and elucidate the relationship between their composition, source, and depositional environment.MethodsUsing gas chromatography-mass spectrometry (GC-MS), we analyzed saturate and aromatic fractions of 41 crude oils from the Xihu Depression, then applied multivariate statistical analysis to classify them based on key biomarker parameters.Results and discussionThe results indicate that the oils are enriched in biomarkers reflecting substantial contributions from terrestrial higher plants, particularly tricyclic diterpanes and their aromatized derivatives originating from angiosperms, gymnosperms, and ferns. In contrast, biomarkers indicative of contributions from aquatic lower organisms were present in relatively low concentrations. Significant variations in the composition of these biomarkers across different structural zones were observed. Statistical analysis of these compositional differences allowed for the classification of the crude oils into four distinct groups. The four categories reflect varying inputs from ferns, gymnosperms, and angiosperms. A new (isopimarane+1,7-DMP)/(16β(H)phyllocladane+retene), effectively assesses gymnosperm versus fern inputs. Higher values of this index indicate a greater gymnosperm contribution. A positive correlation between this index and δ13Coil values highlights the pivotal role of gymnosperm resins in hydrocarbon generation within the Xihu Depression.